Dehydration and performance during prolonged, intermittent table tennis bouts at high ambient temperature - Kobayashi, Y.; Takeuchi, T.; Hosoi, T.; Takaba, S. (Journal of Sports Sciences, 2006)
Table tennis has recently been considered as an attractive leisure time activity to combat inactivity and the risk of associated diseases. It is a convenient, moderate intensity exercise, but often played in facilities not adequate to prevent seasonal heat stress. This study compared cardiovascular and thermoregulatory stress during prolonged, simulated intermittent table tennis bouts (8 X 10-min bouts with 3-min rest intervals) at high ambient temperatures (30ºC, 70% RH) with (HF) and without (H0) fluid intake and at a moderate environment (M0: 17ºC, 50% RH). Eight 20-yr old competitive table tennis players were matched in the 3 environmental conditions against a robot that delivered 60 balls per min. The graded performance task was to return the ball to a target area on the distal end of the table which was 1/8 the table area. Before and during rest periods in HF the subjects drank a commercial sport drink (6.7% glucose, 21 mEq/L Na+) ad libitum. Rectal temperature (Tre-Fig. 1) and heart rate (HR) were significantly higher (p<0.01) during H0 than HF, but Tre and HR were not different between HF and M0. Midway through the trials (50 min) and after the last bout (100 min) during H0, the plasma volume was markedly reduced by 6.5%, which was significantly more than the 3% decline during HF and M0. During H0 the plasma osmolality increased significantly more than during HF and M0. The intake of the carbohydrate-electrolyte fluid during HF did not significantly affect plasma lactate, but reduced free fatty acid and increased glucose blood levels. The fluid intake was effective in maintaining physical performance, in that the significant deteriorations in anaerobic power (jump test) and table tennis performance score during H0 were prevented during HF and values were similar to those during M0 (Fig. 2). The reduced table tennis performance and anaerobic power tests during H0 were closely associated with elevated Tre, HR and plasma volume loss, all attenuated by the fluid intake. The precise mechanism by which the fine motor performance decrement was brought about during H0 is unclear. However, the study shows that fluid intake during prolonged, moderate exercise is important to maintain fine motor performance by skilled players. Also, because table tennis has increased in popularity as a recreational activity for fitness and health, adequate fluid intake at high temperatures may also prevent medical complications in unfit individuals.